Overexpression of the VvSWEET4 Transporter in Grapevine Hairy Roots Increases Sugar Transport and Contents and Enhances Resistance to Pythium irregulare, a Soilborne Pathogen - Meteier, Eloïse; La Camera, Sylvain; Goddard, Mary-Lorène; Laloue, Hélène; Mestre, Pere; Chong, Julie (Frontiers in Plant Science, 2019)
Sugar transport and partitioning play key roles in the regulation of plant development and responses to biotic and abiotic factors. During plant/pathogen interactions, there is a competition for sugar that is controlled by membrane transporters and their regulation is decisive for the outcome of the interaction. SWEET proteins are a class of sugar transporters playing important roles in the first step in phloem loading, in nectar production as well as in seed and pollen development. SWEET transporters are the targets of extracellular pathogens, which modify their expression to acquire the sugars necessary to their growth (Chen et al., 2010). Grapevine (Vitis vinifera) is an economically important crop that is susceptible to diverse pathogens. The regulation of carbon allocation and sugar partitioning in the interaction between grapevine and its pathogens is poorly understood. We previously characterized the SWEET family in V. vinifera and showed that SWEET4 could be involved in resistance to the necrotrophic fungus B. cinerea in Arabidopsis (Chong et al., 2014). To study the role of VvSWEET4 in grapevine, we produced Vitis vinifera cv. Syrah hairy roots overexpressing VvSWEET4 under the control of the CaMV 35S promoter (VvSWEET4OX). High levels of VvSWEET4 expression in hairy roots resulted in enhanced growth on media containing glucose or sucrose and increased contents in glucose and fructose. Sugar uptake assays further showed an improved glucose absorption in VvSWEET4 overexpressors. In parallel, we observed that VvSWEET4 expression was significantly induced after infection of wild type grapevine hairy roots with Pythium irregulare, a soilborne necrotrophic pathogen. Importantly, grapevine hairy roots overexpressing VvSWEET4 exhibited an improved resistance level to P. irregulare infection. This resistance phenotype was correlated to higher glucose pools in roots after infection, higher constitutive expression of several genes involved in flavonoid biosynthesis, and higher flavanol contents. We propose that high sugar levels in VvSWEET4OX hairy roots provides a better support to the increased energy demand during pathogen infection. In addition, high sugar levels promote biosynthesis of flavonoids with antifungal properties. Overall, this work highlights the key role of sugar transport mediated by SWEET transporters for secondary metabolism regulation and pathogen resistance in grapevine.